Long-acting anti-rust oil and preparation process thereof

By using snail mucus extract and polyurethane aqueous solution as film forming components in anti-rust oil, a highly elastic and wear-resistant oil film is solved, and the existing anti-rust oil film is prone to rupture, which significantly improves the anti-rust performance and the strength of the oil film.

CN119709299APending Publication Date: 2025-03-28DONGGUAN YINGFEITE LUBRICATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411888701.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing anti-rust oil can easily cause the oil film to rupture during the handling and stacking of metal workpieces, causing metal rust. How to improve the strength and anti-rust performance of the oil film is a difficult point.

Method used

A long-acting anti-rust oil is used, and its components include base oil components, anti-rust components, film forming components, auxiliary solvent components, thixotropic components and anti-oxidant components. Among them, the film-forming component is composed of snail mucus extract and polyurethane aqueous solution. The snail mucus extract is extracted and separated by stirring and centrifugation, and combined with the polyurethane aqueous solution to form a highly elastic and wear-resistant oil film.

Benefits of technology

The formed oil film has high strength, good adhesion and durability, which can effectively isolate air and moisture, significantly improve anti-rust performance, and extend the service life of the metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200037350000081
    Figure BDA0005200037350000081
Patent Text Reader

Abstract

The invention provides long-acting anti-rust oil and a preparation process thereof. The long-acting anti-rust oil is prepared from the following raw materials in parts by weight: 70.0 to 90.0 parts of a base oil component, 10.0 to 15.0 parts of an anti-rust component, 5.0 to 10.0 parts of a film-forming component, 3.0 to 5.0 parts of a solubilizing component, 3.0 to 5.0 parts of a thixotropic component and 0.5 to 1.0 part of an antioxidant component. Wherein the film forming component is composed of a snail mucus extracting solution and a polyurethane aqueous solution according to the volume ratio of (1-3): (2-4), and the base oil component is composed of mineral oil with the viscosity index of 150, mineral oil with the viscosity index of 500 and poly-alpha olefin ester oil according to the volume ratio of (3-5): (2-4): (1-3). The snail mucus extracting solution and the polyurethane aqueous solution in the film-forming component have a synergistic effect, so that the oil film strength of the anti-rust oil is remarkably improved, and metal is more effectively protected from being damaged by corrosion. When the mineral oil with the viscosity index of 150, the mineral oil with the viscosity index of 500 and the poly-alpha olefin ester oil in the base oil components are mixed according to a certain proportion, the interaction and complementarity among the mineral oil with the viscosity index of 150, the mineral oil with the viscosity index of 500 and the poly-alpha olefin ester oil can be brought into full play, and the performance of the anti-rust oil is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rust-proof oil, and in particular to a long-acting rust-proof oil and a preparation process thereof. Background Art

[0002] As an important engineering material, metal is widely used in various industries such as machinery, construction, transportation, and electronics. It is an indispensable basic element in modern society. However, the corrosion-prone nature of metals has brought considerable challenges to their application. In order to extend the service life of metals and maintain their good performance and appearance, it is particularly important to treat metals with rust prevention. Among the many rust prevention methods, coating rust prevention oil is the most common and effective way. Rust prevention oil can form a protective film on the metal surface, effectively isolating air, moisture, and corrosive media, thereby preventing metal oxidation and corrosion. This protection method is not only simple and easy, but also relatively low in cost, and is suitable for metal products of various shapes and sizes. Common types of rust prevention oils are diverse, including solvent-diluted rust prevention oils, sealed rust prevention oils, emulsified rust prevention oils, and lubricating oil-type rust prevention oils. Among them, solvent-diluted rust prevention oils evaporate quickly after coating, and a protective film is formed quickly, which is suitable for rust prevention of large-scale mechanical equipment. Sealed rust prevention oils are widely used for long-term sealing of metal products due to their thin oil film and easy unsealing. Emulsified anti-rust oil uses water as a diluent, is environmentally friendly, and is mostly used for rust prevention between processes. Lubricating oil anti-rust oil has both anti-rust and lubrication functions. However, no matter which type of anti-rust oil is used, after the workpiece is coated with anti-rust oil, it is easy to cause the oil film to rupture during transportation and stacking, causing the workpiece to rust. Therefore, how to improve the oil film strength to obtain anti-rust oil with good rust prevention performance is a difficult point. Summary of the invention

[0003] In view of this, the present invention proposes a long-lasting anti-rust oil and a preparation process thereof to solve the above problems.

[0004] The technical solution of the present invention is achieved as follows: a long-term anti-rust oil comprises the following raw materials in parts by weight: 70.0-90.0 parts of a base oil component, 10.0-15.0 parts of an anti-rust component, 5.0-10.0 parts of a film-forming component, 3.0-5.0 parts of a solubilizing component, 3.0-5.0 parts of a thixotropic component, and 0.5-1.0 parts of an antioxidant component. The film-forming component is composed of a snail mucus extract and a polyurethane aqueous solution in a volume ratio of (1-3):(2-4).

[0005] Furthermore, a long-lasting anti-rust oil comprises the following raw materials in parts by weight: 80.0 parts of a base oil component, 12.5 parts of an anti-rust component, 7.5 parts of a film-forming component, 4.0 parts of a solubilizing component, 4.0 parts of a thixotropic component, and 0.8 parts of an antioxidant component.

[0006] Furthermore, the base oil component is composed of mineral oil with a viscosity index of 150, mineral oil with a viscosity index of 500, and polyalphaolefin ester oil in a volume ratio of (3-5):(2-4):(1-3).

[0007] Furthermore, the anti-rust component is one or a combination of sodium nitrite, sodium benzoate, sodium tripolyphosphate, sodium pyrophosphate, sodium molybdate, boric acid, urotropine, and benzotriazole.

[0008] Furthermore, the solubilizing component is composed of ethanol, dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of (1-3):(1-3):(0.5-1.5).

[0009] Furthermore, the thixotropic component is one or a combination of carrageenan, gelatin, guar gum, xanthan gum, hydrogenated castor oil, microcrystalline cellulose, sodium carboxymethyl cellulose, polyethylene wax, and polyamide wax.

[0010] Furthermore, the antioxidant component is one or a combination of 2,6-di-tert-butyl-p-cresol, tert-butyl hydroxyanisole, dilauryl thiodipropionate, ascorbyl palmitate, phosphite, and dialkyl dithiocarbamate.

[0011] Furthermore, the snail mucus extract is obtained by the following method: using uncontaminated African snails as raw materials, taking out the snail meat and rinsing it with tap water for 1-3 times, then using a meat slicer to cut the snail meat into 5-10 mm sizes, placing the cut snail meat into a stirring device, and adding 20-40% of the mass of the snail meat into the device. Pure water is stirred at 500-1500rpm for 15-25min; after the stirring is completed, the snail meat is filtered out and the filtrate is taken; the filtrate is allowed to stand for 2-4h, and then the lower layer of mucus is taken; the lower layer of mucus is placed in a centrifuge, centrifuged at 3000-5000rpm for 10-20min, and the upper layer of mucus is taken; then the upper layer of mucus taken out is placed under ultraviolet light for disinfection for 10-30s to obtain the snail mucus extract.

[0012] Furthermore, the polyalphaolefin ester oil is prepared by the following method: adding a polyalphaolefin with a viscosity index of 100-200 to a reaction container, then adding acetic anhydride and p-toluenesulfonic acid, stirring and mixing uniformly, wherein the mass volume ratio of the polyalphaolefin, acetic anhydride and p-toluenesulfonic acid added is (1.0-1.2):(1.0-2.0):(0.05-0.1) g / mL; raising the temperature to 100-150°C and keeping the temperature constant, reacting while stirring for 6-10 hours; after the reaction is completed, neutralizing the reaction with a sodium bicarbonate solution with a mass concentration of 5-10wt%; then washing the reaction product with deionized water, dehydrating the washed reaction product, and then drying the dehydrated reaction product with anhydrous sodium sulfate to obtain the polyalphaolefin ester oil.

[0013] Furthermore, a preparation process of a long-lasting anti-rust oil comprises the following steps:

[0014] S1. Add the base oil component into a stirring device, add the film-forming component thereto, and stir at 200-500 rpm for 30-40 min to obtain a mixed solution I;

[0015] S2, adding the anti-rust component to the mixed solution I, stirring at 150-400 rpm for 25-35 min, to obtain a mixed solution II;

[0016] S3, adding the solubilizing component to the mixed solution II, stirring at 100-300 rpm for 15-25 min, to obtain a mixed solution III;

[0017] S4. Add thixotropic component and antioxidant component to mixed solution III, and stir at 150-400 rpm for 30-40 minutes to obtain a long-lasting anti-rust oil.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The snail mucus extract in the film-forming component of the present invention can form a thin film with excellent elasticity and wear resistance. This thin film can fit tightly on the metal surface, effectively isolating air and moisture, thereby preventing the metal from rusting. At the same time, the natural components of snail mucus make it have good biocompatibility and environmental friendliness, and can provide a good adhesion basis for the polyurethane aqueous solution. In addition, the polyurethane aqueous solution can further form a denser oil film on the preliminary film formed by the snail mucus extract. This oil film can enhance the overall adhesion and durability of the anti-rust oil, and improve the impact resistance and wear resistance of the oil film. When the oil film is subjected to external force, the elasticity of the polyurethane can absorb part of the impact energy, thereby protecting the oil film from damage. The synergistic effect of the two significantly improves the oil film strength of the anti-rust oil, thereby more effectively protecting the metal from rust.

[0020] 2. The mineral oil with a viscosity index of 150, the mineral oil with a viscosity index of 500, and the polyalphaolefin ester oil in the base oil component of the present invention have differences in molecular chain and molecular weight. When used in combination in a specific ratio, the formed oil film can cover and fill pores of different sizes, thereby further improving the bonding ability between the oil film and the workpiece, and the formed oil film is also denser and has higher strength. When these three oils are mixed in a certain ratio, the interaction and complementarity between them can be fully exerted. DETAILED DESCRIPTION

[0021] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0022] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0023] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0024] Example 1

[0025] A long-lasting anti-rust oil comprises the following raw materials in parts by weight: 70.0 parts of a base oil component, 10.0 parts of an anti-rust component, 5.0 parts of a film-forming component, 3.0 parts of a solubilizing component, 3.0 parts of a thixotropic component, and 0.5 parts of an antioxidant component. The base oil component is composed of a mineral oil with a viscosity index of 150, a mineral oil with a viscosity index of 500, and a poly-alpha-olefin ester oil in a volume ratio of 3:2:1, the anti-rust component is sodium nitrite, the film-forming component is composed of a snail mucus extract and a polyurethane aqueous solution in a volume ratio of 1:2, the solubilizing component is composed of ethanol, dimethyl sulfoxide, and N-methylpyrrolidone in a volume ratio of 1:1:0.5, the thixotropic component is carrageenan, and the antioxidant component is 2,6-di-tert-butyl-p-cresol.

[0026] The snail mucus extract is obtained by the following method: using uncontaminated African snails as raw materials, taking out the snail meat and rinsing it with tap water once, then using a meat slicer to cut the snail meat into 5mm sizes, placing the snail meat after cutting into small pieces in a stirring device, adding pure water with a weight of 20% of the snail meat mass into the device, and stirring at 500rpm for 25min; after stirring, filtering out the snail meat and taking the filtrate; letting the filtrate stand for 2h, and then taking the lower layer of mucus; placing the lower layer of mucus in a centrifuge, centrifuging at 3000rpm for 20min, and taking the upper layer of mucus; then placing the taken upper layer of mucus under ultraviolet light for disinfection for 10s, and thus obtaining the snail mucus extract.

[0027] The polyalphaolefin ester oil is prepared by the following method: adding a polyalphaolefin with a viscosity index of 100 to a reaction container, then adding acetic anhydride and p-toluenesulfonic acid, stirring and mixing evenly, wherein the mass volume ratio of the added polyalphaolefin, acetic anhydride and p-toluenesulfonic acid is 1.0:1.0:0.05 g / mL; raising the temperature to 100°C and keeping the temperature constant, reacting while stirring for 10 hours; after the reaction is completed, neutralizing the reaction with a sodium bicarbonate solution with a mass concentration of 5wt%; then washing the reaction product with deionized water, dehydrating the washed reaction product, and then drying the dehydrated reaction product with anhydrous sodium sulfate to obtain the polyalphaolefin ester oil.

[0028] Example 2

[0029] A long-lasting anti-rust oil comprises the following raw materials in parts by weight: 90.0 parts of a base oil component, 15.0 parts of an anti-rust component, 10.0 parts of a film-forming component, 5.0 parts of a solubilizing component, 5.0 parts of a thixotropic component, and 1.0 parts of an antioxidant component. The base oil component is composed of a mineral oil with a viscosity index of 150, a mineral oil with a viscosity index of 500, and a polyalphaolefin ester oil in a volume ratio of 5:4:3, the anti-rust component is composed of sodium tripolyphosphate and boric acid in a mass ratio of 1:1, the film-forming component is composed of a snail mucus extract and a polyurethane aqueous solution in a volume ratio of 3:4, the solubilizing component is composed of ethanol, dimethyl sulfoxide, and N-methylpyrrolidone in a volume ratio of 3:3:1.5, the thixotropic component is composed of gelatin, hydrogenated castor oil, and microcrystalline cellulose in a mass volume ratio of g / mL of 1:1:1, and the antioxidant component is composed of tert-butyl hydroxyanisole and ascorbyl palmitate in a mass ratio of 1:1.

[0030] The snail mucus extract is obtained by the following method: using uncontaminated African snails as raw materials, taking out the snail meat and rinsing it with tap water for 3 times, then using a meat slicer to cut the snail meat into 10 mm sizes, placing the snail meat after cutting into small pieces in a stirring device, adding 40% pure water of the snail meat mass into the device, and stirring at 1500rpm for 15min; after the stirring is completed, filtering out the snail meat and taking the filtrate; letting the filtrate stand for 4h, and then taking the lower layer of mucus; placing the lower layer of mucus in a centrifuge, centrifuging at 5000rpm for 10min, and taking the upper layer of mucus; then placing the taken upper layer of mucus under ultraviolet light for disinfection for 30s, and thus obtaining the snail mucus extract.

[0031] The polyalphaolefin ester oil is prepared by the following method: adding polyalphaolefin with a viscosity index of 200 to a reaction container, then adding acetic anhydride and p-toluenesulfonic acid, stirring and mixing evenly, wherein the mass volume ratio of the added polyalphaolefin, acetic anhydride and p-toluenesulfonic acid is 1.2:2.0:0.1 g / mL; raising the temperature to 150°C and keeping the temperature constant, reacting while stirring for 6 hours; after the reaction is completed, neutralizing the reaction with a sodium bicarbonate solution with a mass concentration of 10wt%; then washing the reaction product with deionized water, dehydrating the washed reaction product, and then drying the dehydrated reaction product with anhydrous sodium sulfate to obtain the polyalphaolefin ester oil.

[0032] Example 3

[0033] A long-lasting anti-rust oil comprises the following raw materials in parts by weight: 80.0 parts of a base oil component, 12.5 parts of an anti-rust component, 7.5 parts of a film-forming component, 4.0 parts of a solubilizing component, 4.0 parts of a thixotropic component, and 0.8 parts of an antioxidant component. The base oil component is composed of a mineral oil with a viscosity index of 150, a mineral oil with a viscosity index of 500, and a polyalphaolefin ester oil in a volume ratio of 4:3:2, the anti-rust component is composed of sodium pyrophosphate, hexamethylenetetramine, and benzotriazole in a mass ratio of 1:1:1, the film-forming component is composed of a snail mucus extract and a polyurethane aqueous solution in a volume ratio of 2:3, the solubilizing component is composed of ethanol, dimethyl sulfoxide, and N-methylpyrrolidone in a volume ratio of 2:2:1, the thixotropic component is composed of sodium carboxymethyl cellulose and polyethylene wax in a mass ratio of 1:1, and the antioxidant component is composed of dilauryl thiodipropionate and dialkyl dithiocarbamate in a mass ratio of 1:1.

[0034] The snail mucus extract is obtained by the following method: using uncontaminated African snails as raw materials, taking out the snail meat and rinsing it with tap water twice, then using a meat slicer to cut the snail meat into 8mm sizes, placing the snail meat after cutting into small pieces in a stirring device, adding pure water with a weight of 30% of the snail meat mass into the device, and stirring at 1000rpm for 20min; after the stirring is completed, filtering out the snail meat and taking the filtrate; letting the filtrate stand for 3h, and then taking the lower layer of mucus; placing the lower layer of mucus in a centrifuge, centrifuging at 4000rpm for 15min, and taking the upper layer of mucus; then placing the taken upper layer of mucus under ultraviolet light for disinfection for 20s, and thus obtaining the snail mucus extract.

[0035] The polyalphaolefin ester oil is prepared by the following method: adding polyalphaolefin with a viscosity index of 150 into a reaction container, then adding acetic anhydride and p-toluenesulfonic acid, stirring and mixing evenly, wherein the mass volume ratio of the added polyalphaolefin, acetic anhydride and p-toluenesulfonic acid is 1.1:1.5:0.08 g / mL; raising the temperature to 125°C and keeping the temperature constant, reacting while stirring for 8 hours; after the reaction is completed, neutralizing the reaction with a sodium bicarbonate solution with a mass concentration of 7wt%; then washing the reaction product with deionized water, dehydrating the washed reaction product, and then drying the dehydrated reaction product with anhydrous sodium sulfate to obtain the polyalphaolefin ester oil.

[0036] The long-lasting anti-rust oil described in the above embodiments 1-3 is prepared by the following process, which specifically includes the following steps:

[0037] S1. Add the base oil component into a stirring device, add the film-forming component thereto, and stir at 350 rpm for 35 min to obtain a mixed solution I;

[0038] S2, adding the anti-rust component to the mixed solution I, stirring at 250 rpm for 30 min, to obtain a mixed solution II;

[0039] S3, adding the solubilizing component to the mixed solution II, stirring at 200 rpm for 20 min, to obtain a mixed solution III;

[0040] S4. Add thixotropic component and antioxidant component to mixed solution III, stir at 250 rpm for 35 min, and obtain a long-lasting anti-rust oil.

[0041] Example 4

[0042] Compared with Example 3, this embodiment is different in that the long-lasting anti-rust oil is prepared by the following process, which specifically includes the following steps:

[0043] S1. Add the base oil component into a stirring device, add the film-forming component thereto, and stir at 200 rpm for 40 min to obtain a mixed solution I;

[0044] S2, adding the anti-rust component to the mixed solution I, stirring at 150 rpm for 35 min, to obtain a mixed solution II;

[0045] S3, adding the solubilizing component to the mixed solution II, stirring at 100 rpm for 25 min, to obtain a mixed solution III;

[0046] S4. Add thixotropic component and antioxidant component to mixed solution III, and stir at 150 rpm for 40 minutes to obtain a long-lasting anti-rust oil.

[0047] Example 5

[0048] Compared with Example 3, the difference between Example 3 and Example 3 is that the long-lasting anti-rust oil is prepared by the following process, which specifically includes the following steps:

[0049] S1. Add the base oil component into a stirring device, add the film-forming component thereto, and stir at 500 rpm for 30 min to obtain a mixed solution I;

[0050] S2, adding the anti-rust component to the mixed solution I, stirring at 400 rpm for 25 min, to obtain a mixed solution II;

[0051] S3, adding the solubilizing component to the mixed solution II, stirring at 300 rpm for 15 min, to obtain a mixed solution III;

[0052] S4. Add thixotropic component and antioxidant component to mixed solution III, stir at 400 rpm for 30 min, and obtain a long-lasting anti-rust oil.

[0053] Comparative Example 1

[0054] The difference between this comparative example and Example 3 is that the film-forming component is a single snail mucus extract.

[0055] Comparative Example 2

[0056] The difference between this comparative example and Example 3 is that the film-forming component is a single polyurethane aqueous solution.

[0057] Comparative Example 3

[0058] This comparative example is compared with Example 3, the difference is that the base oil component is a single mineral oil with a viscosity index of 150

[0059] Comparative Example 4

[0060] The difference between this comparative example and Example 3 is that the base oil component consists of a mineral oil with a viscosity index of 150 and a mineral oil with a viscosity index of 500 in a volume ratio of 4:3.

[0061] The difference between this comparative example and Example 3 is that the rust-proof liquid is a commercially available rust-proof liquid.

[0062] 1. Oil film strength test

[0063] 50 pieces of 10# carbon steel sheets with a size of 100mm×50mm×1mm, which are oil-free, rust-free and have a surface roughness of Ra1.6, were selected as test pieces. The test pieces were randomly divided into 10 groups. The surface of the steel sheets was first wiped with anhydrous ethanol to ensure complete drying. Then each group was coated with the anti-rust oil prepared in Examples 1-5 and Comparative Examples 1-5, with a coating thickness of 20μm. After coating, the test pieces were placed at room temperature to dry naturally and waited for 24h. Then the test pieces coated with anti-rust oil were installed in the pressure testing device, and the pressure testing device was started to gradually increase the pressure applied to the test pieces at a constant rate of 1MPa per minute. Observe and record the pressure value when the oil film ruptures. The pressure value when the oil film ruptures is the oil film strength. The average value of the oil film strength of each group was calculated. The results are shown in Table 1.

[0064] Table 1

[0065]

[0066] It can be seen from Table 1 that the oil film strength of the rust-proof oil prepared in Examples 1-5 is much higher than that of Comparative Examples 1-5. It can be seen that the rust-proof oil prepared in the present invention can form a high-strength oil film on the surface of the workpiece, so that the rust-proof oil obtains long-term rust-proof performance.

[0067] By comparing Example 3 in Table 1 with Comparative Examples 1-2, it can be found that the oil film formed can be made stronger only when the snail mucus extract and the polyurethane aqueous solution act together. This is because the snail mucus extract can form a thin film with excellent elasticity and wear resistance, which can fit tightly on the metal surface, effectively isolating air and moisture, thereby preventing the metal from rusting. At the same time, the natural ingredients of snail mucus give it good biocompatibility and environmental friendliness, and can provide a good adhesion basis for the polyurethane aqueous solution. In addition, the polyurethane aqueous solution can further form a denser oil film on the preliminary film formed by the snail mucus extract. This oil film can enhance the overall adhesion and durability of the anti-rust oil and improve the impact resistance and wear resistance of the oil film. When the oil film is subjected to external force, the elasticity of the polyurethane can absorb part of the impact energy, thereby protecting the oil film from damage. Hydrogen bonds can be formed between the carbamate bonds in the aminoester aqueous solution and the hydroxyl, carboxyl and other groups in the snail mucus extract. The presence of these hydrogen bonds makes the molecular chains of the two film-forming components intertwined with each other, forming a tighter network structure, thereby enhancing the adhesion and stability of the oil film. The isocyanate groups in the aqueous urethane solution can react with the hydroxyl, amino and other groups in the snail mucus extract to form urea bonds or carbamate bonds. The formation of these covalent bonds tightly connects the polyurethane aqueous solution and the snail mucus extract to form a stable cross-linked structure. The synergistic effect of the two significantly improves the film strength of the rust-proof oil, thereby more effectively protecting the metal from rust.

[0068] By comparing Example 3 with Comparative Examples 3-4 in Table 1, it can be found that when the mineral oil with a viscosity index of 150, the mineral oil with a viscosity index of 500, and the polyalphaolefin ester oil act together, the oil film strength formed can be higher. The base oil component plays a carrier role on the one hand, and participates in the formation of the rust-proof oil film on the other hand. The mineral oil with a viscosity index of 150, the mineral oil with a viscosity index of 500, and the polyalphaolefin ester oil in Example 3 have differences in molecular chain and molecular weight. When used in combination in a specific ratio, the oil film formed can cover and fill pores of different sizes, thereby further improving the bonding ability of the oil film with the workpiece, and the oil film formed is also denser and has higher strength. When these three oils are mixed in a certain proportion, the interaction and complementarity between them can be fully exerted. The mineral oil with a viscosity index of 150 and the mineral oil with a viscosity index of 500 are attached to the workpiece surface through physical adsorption, and the polyalphaolefin ester oil can form chemical adsorption with the metal surface. The ester groups contained in polyalphaolefin ester oil can form coordination bonds or ionic bonds with metal ions on the metal surface, thereby enhancing the adhesion between the oil film and the metal. The synergistic effect of this chemical adsorption and physical adsorption helps the oil film to fit more closely to the metal surface, forming a tougher and more durable oil film. Under this synergistic effect, the strength of the oil film of the rust-proof oil has been significantly improved. The oil film can not only fit closely to the metal surface to form an effective protective barrier, but also resist the damage of various corrosive substances and mechanical stress from the outside.

[0069] 2. Anti-rust performance test

[0070] 50 pieces of 10# carbon steel sheets with a size of 100mm×50mm×1mm, which are oil-free, rust-free and have a surface roughness of Ra1.6, were selected as test pieces. The test pieces were randomly divided into 10 groups. The surface of the steel sheets was first wiped with anhydrous ethanol to ensure complete drying. Then, each group was coated with the anti-rust oil prepared in Examples 1-5 and Comparative Examples 1-5, with a coating thickness of 20 μm. The tests were carried out according to the following test requirements.

[0071] 2.1 Neutral salt spray test

[0072] 50 pieces of oil-free, rust-free 45# carbon steel sheets with a size of 80mm×60mm×3mm were selected as test pieces. The above test pieces were randomly divided into 10 groups. The surface of the steel sheet was first wiped with anhydrous ethanol to ensure complete drying. Then, the anti-rust oil prepared in Examples 1-5 and Comparative Examples 1-5 was applied to the test pieces of each group according to SH / T0081-1991 "Rust-proof Grease Salt Spray Test Method", and dried as required. The above test pieces were placed in a salt spray test box and tested according to the above standards. The test was continued until rust appeared, and the required time was recorded. The average time required for rust to appear was calculated for each group as the salt spray test time, and the results were recorded in Table 2.

[0073] 2.2 Damp heat test

[0074] 50 pieces of oil-free, rust-free 45# carbon steel sheets with a size of 80mm×60mm×3mm were selected as test pieces. The test pieces were randomly divided into 10 groups. The surface of the steel sheets was first wiped with anhydrous ethanol to ensure complete drying. Then, the anti-rust oil prepared in Examples 1-5 and Comparative Examples 1-5 was applied to the test pieces of each group according to GB / T2361-1992 "Rust-proof Grease Wet Heat Test Method", and dried as required. The test pieces were placed in a salt spray test box and tested according to the above standards. The test was continued until rust appeared, and the required time was recorded. The average time required for rust to appear was calculated for each group as the wet heat test time, and the results were recorded in Table 2.

[0075] Table 2

[0076] Salt spray test time / h Wet heat test time / d Example 1 126 56 Example 2 124 57 Example 3 130 59 Example 4 125 55 Example 5 123 57 Comparative Example 1 91 39 Comparative Example 2 97 43 Comparative Example 3 95 42 Comparative Example 4 101 49 Comparative Example 5 74 32

[0077] As can be seen from Table 2, the salt spray resistance and moisture and heat resistance of Examples 1-5 are better than those of Comparative Examples 1-5. The snail mucus extract and polyurethane aqueous solution in the film-forming component of the present invention form a dense and continuous protective film on the surface of the workpiece. This film can isolate the workpiece from direct contact with the external environment, thereby slowing down or preventing the rust process. The polyurethane aqueous solution has good adhesion and elasticity, can firmly adhere to the surface of the workpiece, and is not easy to fall off. The snail mucus extract contains natural adhesive components, which further enhance the adhesion and durability of the film. In addition, the snail mucus extract contains self-repairing ability, and when the film layer is slightly damaged, it can heal automatically, thereby maintaining the integrity of the film. On the one hand, the base oil component of the present invention acts as a carrier of the anti-rust component to evenly disperse and transport the rust inhibitor to the surface of the workpiece. On the other hand, the base oil has good lubricity and permeability, and can penetrate into the tiny gaps and pores on the surface of the workpiece, which helps the anti-rust component to act more deeply on the surface of the workpiece to form a more comprehensive protection. The base oil component interacts with the film-forming component to form a more stable and durable protective film. Thus, the anti-aging and anti-corrosion capabilities of the film are improved, thereby prolonging the effect of the anti-rust oil. The adhesion and elasticity of the film-forming component ensure the firmness and durability of the film, while the lubricity and permeability of the base oil component enhance the coverage and depth of the protective film. The combined effect of the film-forming component and the base oil component enables the anti-rust oil of the present invention to have a long-term anti-rust ability and endow the coated workpiece with excellent salt spray resistance and moisture and heat resistance.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A long-lasting anti-rust oil, characterized in that: The invention comprises the following raw materials in parts by weight: 70.0-90.0 parts of a base oil component, 10.0-15.0 parts of a rust-proof component, 5.0-10.0 parts of a film-forming component, 3.0-5.0 parts of a solubilizing component, 3.0-5.0 parts of a thixotropic component, and 0.5-1.0 parts of an antioxidant component. The film-forming component is composed of a snail mucus extract and a polyurethane aqueous solution in a volume ratio of (1-3):(2-4).

2. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 80.0 parts of base oil component, 12.5 parts of rust-proof component, 7.5 parts of film-forming component, 4.0 parts of solubilizing component, 4.0 parts of thixotropic component and 0.8 parts of antioxidant component.

3. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The base oil component is composed of mineral oil with a viscosity index of 150, mineral oil with a viscosity index of 500, and polyalphaolefin ester oil in a volume ratio of (3-5):(2-4):(1-3).

4. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The anti-rust component is one or a combination of sodium nitrite, sodium benzoate, sodium tripolyphosphate, sodium pyrophosphate, sodium molybdate, boric acid, hexamethylenetetramine, and benzotriazole.

5. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The solubilizing component is composed of ethanol, dimethyl sulfoxide and N-methyl pyrrolidone in a volume ratio of (1-3):(1-3):(0.5-1.5).

6. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The thixotropic component is one or a combination of carrageenan, gelatin, guar gum, xanthan gum, hydrogenated castor oil, microcrystalline cellulose, sodium carboxymethyl cellulose, polyethylene wax, and polyamide wax.

7. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The antioxidant component is one or a combination of 2,6-di-tert-butyl-p-cresol, tert-butyl hydroxyanisole, dilauryl thiodipropionate, ascorbyl palmitate, phosphite, and dialkyl dithiocarbamate.

8. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The snail mucus extract is obtained by the following method: selecting unpolluted African snails as raw materials, taking out snail meat and rinsing it with tap water for 1-3 times, then using a meat slicer to cut the snail meat into 5-10 mm sizes, placing the snail meat after cutting into a stirring device, and adding 20-40% of the mass of the snail meat into the device. Pure water is stirred at 500-1500rpm for 15-25min; after the stirring is completed, the snail meat is filtered out to obtain the filtrate; the filtrate is allowed to stand for 2-4h, and then the lower layer of mucus is taken; the lower layer of mucus is placed in a centrifuge, centrifuged at 3000-5000rpm for 10-20min, and the upper layer of mucus is taken; and then the upper layer of mucus taken out is placed under ultraviolet light for disinfection for 10-30s to obtain the snail mucus extract.

9. A long-lasting anti-rust oil as claimed in claim 1, characterized in that: The polyalphaolefin ester oil is prepared by the following method: adding a polyalphaolefin with a viscosity index of 100-200 into a reaction container, then adding acetic anhydride and p-toluenesulfonic acid, stirring and mixing evenly, wherein the mass volume ratio of the polyalphaolefin, acetic anhydride and p-toluenesulfonic acid added is (1.0-1.2):(1.0-2.0):(0.05-0.1) g / mL; raising the temperature to 100-150° C. and keeping the temperature constant, reacting while stirring for 6-10 hours; after the reaction is completed, neutralizing the reaction with a sodium bicarbonate solution with a mass concentration of 5-10wt%; then washing the reaction product with deionized water, dehydrating the washed reaction product, and then drying the dehydrated reaction product with anhydrous sodium sulfate to obtain the polyalphaolefin ester oil.

10. A process for preparing a long-acting anti-rust oil according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add the base oil component into a stirring device, add the film-forming component thereto, and stir at 200-500 rpm for 30-40 min to obtain a mixed solution I; S2, adding the anti-rust component to the mixed solution I, stirring at 150-400 rpm for 25-35 min, to obtain a mixed solution II; S3, adding the solubilizing component to the mixed solution II, stirring at 100-300 rpm for 15-25 min, to obtain a mixed solution III; S4. Add thixotropic component and antioxidant component to mixed solution III, and stir at 150-400 rpm for 30-40 minutes to obtain a long-lasting anti-rust oil.